PENERAPAN METODE BUDIDAYA KERAMBA JARING APUNG UNTUK MENINGKATKAN PRODUKSI RUMPUT LAUT PADA KELOMPOK USAHA BERSAMA LAPININDA JAYA DI KABUPATEN BUTON UTARA - Ridwan, Ridwan; Tabia, La Aman; Daud, La Ode Rahman; Isra, Isra; Hania, Selfi (Universitas Mataram, 2024)
Indonesia has significant potential for seaweed production; however, its productivity remains low compared to other countries, hindering optimal sector development. This issue arises from ineffective traditional cultivation methods and insufficient government policies. North Buton Regency, as one of the third-largest seaweed producers in Southeast Sulawesi, faces challenges in seaweed cultivation, particularly due to the use of traditional methods that yield low production and contribute to environmental pollution. This community service program aims to enhance the knowledge and skills of the Lapininda Jaya Joint Business Group in seaweed cultivation techniques through the implementation of the Floating Net Cage (KJA) method. Through participatory training, participants learn to create and manage KJA, select quality seeds, and apply effective management practices. Evaluation results indicate a significant increase in participants' understanding of seaweed and cultivation techniques, with average comprehension scores rising from 22.4 to 26.4 post-training. Additionally, the implementation of KJA has proven to enhance seaweed production yields, providing economic benefits and promoting environmental sustainability. This program not only benefits the partner group but also strengthens institutional capacity and management of aquatic resources.